The stereodynamics of 5,5’-disubstituted BIPHEPs - Maier, Frank; Trapp, Oliver (Chirality, 2013)
We investigated the stereodynamics of 5,5’-substituted tropos BIPHEP ligands (2,2’-bis(diphenylphosphino)-biphenyls) by enantioselective dynamic high-performance liquid chromatography (DHPLC) to elucidate the influence of the substitution pattern and electronics of the substituents (methyl, methoxy, and hydroxyl groups). By temperature-dependent dynamic HPLC measurements the activation parameters ΔG╪, ΔH╪, and ΔS╪ could be determined with high precision, revealing that the activation barrier of these 5,5’-substituted BIPHEP ligands ranges in a narrow band between 87.8 and 93.0 kJ mol-1, making them highly attractive as deracemizable dynamic chiral ligands in asymmetric catalysis. Interestingly, the activation parameters are highly influenced by a hydroxyl or methoxy group in the 5,5’-position of the BIPHEP ligands. Chirality 25:126-132, 2013. © 2012 Wiley Periodicals, Inc.